2004
DOI: 10.4049/jimmunol.173.11.7055
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Phospholipid Antibodies Restore Mesenteric Ischemia/Reperfusion-Induced Injury in Complement Receptor 2/Complement Receptor 1-Deficient Mice

Abstract: Complement receptor 2-deficient (Cr2−/−) mice are resistant to mesenteric ischemia/reperfusion (I/R) injury because they lack a component of the natural Ab repertoire. Neither the nature of the Abs that are involved in I/R injury nor the composition of the target Ag, to which recognition is lacking in Cr2−/− mice, is known. Because anti-phospholipid Abs have been shown to mediate fetal growth retardation and loss when injected into pregnant mice, we performed experiments to determine whether anti-phospholipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 44 publications
(79 reference statements)
4
74
0
Order By: Relevance
“…IRI has been shown to be complement dependent in numerous experimental models, and the demonstration of complement deposition within ischemic tissues would not be unexpected. However, in previous studies, whether or not C3 deposition could be demonstrated in rodent intestine and lung appeared to be dependent on species, length of ischemia, and time of reperfusion (12,14,17). In this study, we demonstrated the presence of C3 in both the intestine and the lung of PBS-treated mice.…”
Section: Effect Of Cr2-crry and Crry-ig On Intestinal Irisupporting
confidence: 50%
See 1 more Smart Citation
“…IRI has been shown to be complement dependent in numerous experimental models, and the demonstration of complement deposition within ischemic tissues would not be unexpected. However, in previous studies, whether or not C3 deposition could be demonstrated in rodent intestine and lung appeared to be dependent on species, length of ischemia, and time of reperfusion (12,14,17). In this study, we demonstrated the presence of C3 in both the intestine and the lung of PBS-treated mice.…”
Section: Effect Of Cr2-crry and Crry-ig On Intestinal Irisupporting
confidence: 50%
“…The role of antibodies in initiating IRI is further supported in other studies using Cr2 -/-mice, which are protected from IRI due to a deficient natural antibody repertoire (8,16). Pretreatment of these mice with IgM and IgG purified from wild-type mice showed that these Ig subclasses can each contribute separately to IRI (16), and it was recently shown that tissue injury can be restored in these mice by reconstitution with antibodies against negatively charged phospholipids or β2 glycoprotein 1 (17). These data indicate that multiple specificities may be involved in antibody interactions with ischemic antigens.…”
Section: Introductionsupporting
confidence: 51%
“…33 C activation proceeds to completion with the assembly of the terminal complex as indicated by the deposition of rat C9. The specificity of this finding is confirmed by our failure to detect bound C9 in aPL IgG-treated C6-deficient rats, while the extent of C3 deposition was similar to that observed in C6-sufficient rats.…”
Section: Discussionmentioning
confidence: 99%
“…57 In several elegant studies, Fleming et al have shown that natural anti-␤ 2 GPI antibodies are involved in complement-mediated mesenteric ischemia/reperfusioninduced injury. 58,59 In addition, there are also indications that natural antiphospholipid antibodies are involved in acute graft rejection after renal transplantation. 60 Natural antibodies are thought to play a role in the clearance of apoptotic bodies and there is convincing evidence that ␤ 2 GPI and anti-␤ 2 GPI antibodies are essential for the clearance of these cell remnants.…”
Section: The Etiology Of Autoantibodies Against ␤ 2 Gpimentioning
confidence: 99%